ASSESSMENT OF GENETIC VARIATION OF PEARL OYSTER, Pinctada maxima, BASED ON THE ANALYSIS OF MITOCHONDRIAL CYTOCHROME OXIDASE SUBUNIT I GENE - Achmad Sudradjat; Rini Susilowati; Imron Imron (Indonesian Aquaculture Journal, 2009)
Pearl oyster, Pinctada maxima is one of economical ly important species in aquaculture, particularly in pearl industry. Information on genetic variation of pearl oyster is required in order to be able to make a sound management of it’s natural populations and to utilize it to improve the quality of pearl culture. Five populations from different geographic locations of pearl oyster, Pinctada maxima, (Sumbawa, Bali, Selat Sunda, Belitung, and South Sulawesi) were analyzed for genetic variation within a 750-base pair region of the Mitochondrial Cytochrome Oxidase subunit I (MtCOI) gene using Restriction Fragment Length Polymorphism (RFLP) technique. The analysis of 25 pearl oyster samples, their haplotype diversity ranged from 0.0970 to 0.1939 and the number of haplotype in each population ranged from three to five haplotypes. Clustering of populations based on Nei’s genetic distances and constructed using unweighted pair-group method with Arithmetic mean (UPGMA) showed that the populations were clustered into two groups: Belitung, Selat Sunda, Bali and Sumbawa in one group, while South Sulawesi in the second group.